2016
DOI: 10.1007/s00294-016-0599-x
|View full text |Cite
|
Sign up to set email alerts
|

Timeless protection of telomeres

Abstract: The DNA replication machinery encounters problems at numerous genomic regions that are inherently difficult to replicate. These genomic regions include telomeres, which contain repetitive DNA and telomere-binding proteins. If not properly regulated, replication of such genomic regions can result in DNA damage, leading to genomic instability. Studies implicated a role of Timeless-related proteins at difficult-to-replicate genomic regions, including telomeres. However, how these proteins maintain telomeres was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The FPC travels with the replisome in order to protect replication fork structures at various RFBs [15,16]. Interestingly, the same study showed that swi1 ∆ mutants display increased DNA damage and recombination at telomeres, leading to activation of ALT-like pathways of telomere maintenance, suggesting a role of Swi1 as an anti-recombinase at the telomere [14,17]. Consistently, depletion of Timeless (human homolog of Swi1) results in increased levels of DNA repair foci and sister chromatid exchange in mouse cells, indicative of elevated levels of homologous recombination [18].…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…The FPC travels with the replisome in order to protect replication fork structures at various RFBs [15,16]. Interestingly, the same study showed that swi1 ∆ mutants display increased DNA damage and recombination at telomeres, leading to activation of ALT-like pathways of telomere maintenance, suggesting a role of Swi1 as an anti-recombinase at the telomere [14,17]. Consistently, depletion of Timeless (human homolog of Swi1) results in increased levels of DNA repair foci and sister chromatid exchange in mouse cells, indicative of elevated levels of homologous recombination [18].…”
Section: Replication Barriers Associated With Repeat Dna and Protementioning
confidence: 99%
“…Mechanistically, at G2/M checkpoint, human Timeless protein interacts with ataxia telangiectasia protein (ATR), a DNA damage sensor kinase, promoting the phosphorylation of Checkpoint kinase 1 leading to cell cycle arrest or apoptosis (97). Additionally, the down-regulation of the Timeless gene in human carcinoma cells shortened telomeres, revealing its importance in maintaining telomere length (96,98). Relatedly, the protein kinase, WEE1 is cell cycle regulator which falls under the influence of the molecular circadian clock.…”
Section: The Clock and Glioma Pathways Of Cell-cycle Regulation Dna-mentioning
confidence: 99%
“…DNA damage associated with telomeres is increased in cells with reduced replication of the Timeless gene, along with disruption of telomere replication. Swi1 is a protein associated with the Timeless protein, which is responsible for DNA replication in the telomere region [53]. Single nucleotide polymorphism in the Timeless gene, which leads to the replacement of glutamine by arginine in the amino acid sequence of the protein, has not demonstrated an association with changes in morning or evening diurnal rhythms in humans [54].…”
Section: The Complex Role Of Molecular Pathways In the Aging Processmentioning
confidence: 99%